AC conductivity and dielectric behavior of poly (o-phenylenediamine)/TiO2 nanocomposites - S., Archana (International Journal of Advanced Chemistry, 2017)
Poly (o-phenylenediamine) and their nanocomposites with TiO2 nanoparticles were synthesized using oxidative polymerization technique and the polymer nanocomposites were characterized using spectral techniques like FT-IR, UV-VIS spectroscopy and the morphology have been analyzed by XRD, SEM and TEM. The stability of the prepared polymer nanocomposites was studied using TGA, DTA and found to have high thermal stability. The study of ac conductivity, dielectric property revealed that the formed nanocomposites are semiconducting in nature and can be widely used in the field of energy storage and semiconductor devices, in diodes, batteries etc.